METODE PENGEMBANGAN SDM MAGANG, ROTASI KERJA, STUDI BANDING DI SDIT AR-RAHMAH MUSTIKAJAYA BEKASI - Alfi, Rochayah Alfi rahmani; Irnie Victorynie (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This study aims to analyze the implementation of human resource development (HRD) methods at SDIT Ar-Rahmah Mustika Jaya Bekasi, specifically focusing on internship, job rotation, and benchmarking. The research was conducted to explore how these methods affect the improvement of the quality of educators and educational staff at the school. The research method used is a qualitative approach with in-depth interviews with the principal, head of HRD, senior teachers, new teachers, and administrative staff to obtain data related to their experiences and views on the implementation of HRD methods at the school. The findings of the study indicate that the implementation of internships, job rotations, and benchmarking successfully enhances educators' competencies, broadens their perspectives on various aspects of education, and creates a more innovative learning environment. Despite challenges in time management and planning, effective coordination among related parties ensures that these methods run effectively. This research contributes to the development of HRD in educational institutions based on Islamic values.